The environmental stability of large-size and single-crystalline antimony flakes grown by chemical vapor deposition on SiO2 substrates. Issue 69 (13th August 2018) - Wu, Qinke; Song, Young Jae
Abstract : The environmental stability of large-sized and single-crystalline antimony flakes was systematically investigated with temperature and time dependence at fixed humidity. Abstract : The environmental stability of large-sized and single-crystalline antimony flakes was systematically investigated with temperature and time dependence at fixed humidity. The antimony flakes used in this work were grown by chemical vapor deposition (CVD) directly on SiO2 substrates, where antimonene layers were stacked to a few tens of nm thickness with a typical area of ∼40 μm.